2018
DOI: 10.1089/gtmb.2017.0277
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis ofLRRK1andLRRK2Variants in Essential Tremor Patients

Abstract: The data suggest that LRRK1 variant (rs2924835) and LRRK2 variants (rs34594498, rs34410987, and rs33949390) are not associated with ET in this Han Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…More precisely, carriers of R1628P appeared to have a two-fold increased risk of ET (p = 0.0035, OR = 2.20) in a cohort consisting mainly of Asians (90%) [86]. However, other examined variants of LRRK1 and LRRK2 genes, in Asian and Non-Hispanic whites cohorts [84,[87][88][89], failed to present any association with ET.…”
Section: Lrrk2 (Leucine-rich Repeat Kinase 2) Lrrk1 (Leucine-rich Rementioning
confidence: 93%
“…More precisely, carriers of R1628P appeared to have a two-fold increased risk of ET (p = 0.0035, OR = 2.20) in a cohort consisting mainly of Asians (90%) [86]. However, other examined variants of LRRK1 and LRRK2 genes, in Asian and Non-Hispanic whites cohorts [84,[87][88][89], failed to present any association with ET.…”
Section: Lrrk2 (Leucine-rich Repeat Kinase 2) Lrrk1 (Leucine-rich Rementioning
confidence: 93%
“…It is estimated that between 20% and 90% of ET patients have a positive family history, which is more frequent in young-onset cases [ 18 , 19 ]. There is a concordance between 60 and 77% in monozygotic twins [ 12 , 20 ].…”
Section: Geneticsmentioning
confidence: 99%
“…The authors tested 26 loci derived from genome-wide association studies in ET patients and found no role for them in PD patients. Similarly, a Chinese group studied LRRK1 and LRKK2 variants (a common cause of monogenic PD) in a cohort of ET patients, again finding no association [ 20 ].…”
Section: Geneticsmentioning
confidence: 99%
“…While a number of studies have failed to identify the causative genes (104)(105)(106)(107)(108)(109)(110)(111), several risk genes appear to have an overlapping role in ET and PD (112). For instance, association studies have found that leucine-rich repeat and immunoglobulin containing 1 gene is involved in the pathogenesis of ET and PD (113)(114)(115)(116)(117)(118) and serves as a potential therapeutic target in these two disorders.…”
Section: Geneticsmentioning
confidence: 99%